2023
DOI: 10.1128/jmbe.00182-22
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate STEM Students’ Science Communication Skills, Science Identity, and Science Self-Efficacy Influence Their Motivations and Behaviors in STEM Community Engagement

Abstract: While numerous studies have examined how scientists perceive doing public communication and engagement, there is limited research on undergraduate science, technology, engineering, and math (STEM) student attitudes toward these meaningful activities. Undergraduate students are more diverse than STEM faculty and may serve as boundary spanners in communities, so exploring their motivations and behaviors in STEM engagement is valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Numerous studies have investigated scientists' perspectives on public engagement and its significance in shaping their professional identity [Besley, Dudo, Yuan & Lawrence, 2018]. In one study by Murphy and Kelp [2023] looking at motivations of undergraduate STEM students in community engagement, authors found science communication skills, science identity, and science self-efficacy were all predictors of student motivation and behaviors in STEM engagement with communities outside of academia. However, the authors note that their study population was disproportionately white and female.…”
Section: Stem Identitymentioning
confidence: 99%
“…Numerous studies have investigated scientists' perspectives on public engagement and its significance in shaping their professional identity [Besley, Dudo, Yuan & Lawrence, 2018]. In one study by Murphy and Kelp [2023] looking at motivations of undergraduate STEM students in community engagement, authors found science communication skills, science identity, and science self-efficacy were all predictors of student motivation and behaviors in STEM engagement with communities outside of academia. However, the authors note that their study population was disproportionately white and female.…”
Section: Stem Identitymentioning
confidence: 99%
“…Since evolutionary theory can present a challenging course of study with students often expressing various misconceptions on the process, further inclusion of evolution education can improve overall knowledge and understanding across disciplines. Recent research indicates that universities should promote student scientific communication training, which could improve undergraduate student skills to lessen miscommunication of public science understanding (Osterhage & Rogers-Carpenter, 2022) and further provide experiential learning scenarios for students following instruction to become involved in community and professional outreach STEM activities (Murphy & Kelp, 2023). This fun, short activity we developed when implemented with other novel teaching strategies which further biological knowledge and science communication in undergraduates may provide a eureka effect for student understanding of the evolutionary importance of fossils.…”
Section: Table 1 Representative Student Responses To Surveymentioning
confidence: 99%
“…Science identity should be viewed as malleable and impacted by student experiences and interactions [16]. Importantly, increases in students’ science identity have been linked to a stronger commitment to a science career [17], persistence and retention in the sciences [15, 18], as well as increases in student motivation and community engagement [19]. Conversely, identity mismatch, whereby students experience uncertainty about how they fit in an academic environment, can result in withdrawal from academic pursuits and opportunities [14].…”
Section: Introductionmentioning
confidence: 99%